The Influence of Liquidity, Leverage, and Company Size on Return On Assets at PT Mayora Indah Tbk, Period 2015–2022, - Fitriana; Rendra Erdkhadifa (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2023)
The purpose of this study was to determine the effect of the variables liquidity, leverage, and company size on the return on assets at PT Mayora Indah Tbk for the 2015–2022 period. This research method uses quantitative research by taking secondary data from the financial statements of PT Mayora Indah Tbk for the period 2015–2022. This study uses multiple regression analysis of 32 samples. The research results show that, partially, the liquidity variable has no significant effect on ROA. While the leverage and company size variables partially have a significant influence on ROA, The variables of liquidity, leverage, and company size all have an effect on ROA. The limitation of this study is that the population used is limited to one manufacturing company listed on the Indonesia Stock Exchange and only uses three independent variables, namely liquidity, leverage, and company size, and one dependent variable, namely return on assets. This research was conducted at food and beverage companies that focused on PT Mayora Indah Tbk in the 2015–2022 period, which had never been done by previous research, so that it could be used as a reference for further research.